Empowering translanguaging practices to encourage language preservation and cultural awareness in vocational EFL classrooms - Margana Margana; Yuyun Yulia; Lu'luil Maknun; Eko Prasetyo Nugroho Saputro (Studies in English Language and Education, 2026)
This study examines the implementation of translanguaging in English as a Foreign Language (EFL) classrooms at vocational high schools in Bantul, Yogyakarta, Indonesia, with an emphasis on its role in supporting students’ comprehension, linguistic sensitivity, and cross-cultural awareness. Recognizing the multilingual reality of Indonesian education, this research specifically explores the students’ perceptions of translanguaging and the impact of its implementation in vocational EFL classrooms. Employing an explanatory sequential mixed methods design, data were collected from 2,171 students and 45 English teachers across ten vocational schools through questionnaires, classroom observations, and semi-structured interviews. This study’s findings revealed that most students perceived translanguaging as beneficial for enhancing confidence, motivation, and classroom participation. Additionally, the impact of translanguaging implementation included facilitating a more profound understanding, strengthening linguistic identities, and promoting cultural reflection. A comparative analysis across schools further demonstrated that flexible bilingual policies encouraged richer interaction and intercultural engagement, whereas monolingual English instructions tended to limit communication and comprehension. The study concludes that translanguaging serves not only as an effective pedagogical strategy but also as a sociocultural practice that supports language preservation and prepares students for multilingual professional environments. The findings further emphasize the importance of institutional support and teacher training in facilitating the effective and appropriate implementation of translanguaging in vocational EFL classrooms.